A review of the utility of PET imaging in Staphylococcus aureus bacteraemia (SAB) using electronic data. Issue 2 (28th February 2020) - Cavaliere, Chiara; Klein, John; Goodman, Anna
Abstract : Introduction: If the infectious focus is not identified, there is an associated higher mortality in Staphylococcus aureus bacteraemia (SAB) [1]. A retrospective observational study found patients with high-risk SAB who had a PET scan had a 67% reduction in mortality compared to those who did not [2]. We used electronic data to determine the range of infectious foci in SAB and the use of PET in our trust. Methods: From 1/1/13 to 31/12/18 all patients with SAB at St Thomas' Hospital, London, were reviewed by the infectious diseases team and data collected prospectively using an Access database. A retrospective analysis of this database, electronic records, radiology and nuclear imaging was conducted. Results: 355 episodes of SAB affected 296 patients. 28 (8%) episodes were MRSA in 24 (8%) of patients. Infectious sources found included bone and joint (23%), IV access (15%), vascular infection (15%), no infective focus (13%), SSTI (12%) and endocarditis (9%). Imaging used to determine the focus of infection included MRI (18%), CT (26%) and PET scan (10%). In-hospital mortality was significantly lower in those who had a PET scan than in those who did not (1/31, 3% v. 50/265 patients (last episode), 19%, P=0.03). Conclusions: Mortality was lower in those who had PET at our trust. This is consistent with data published from other centres and requires further investigation. A prospective trial of PET in SAB is urgently needed. References: [1] PMID: 30179645 [2] PMID: 28336786